Use of additive composition for controlled accelerated degradation of polycondensates

By using a mixture of aliphatic or cycloaliphatic polyols and organophosphorus compounds as hydrolysis catalysts in the polycondensation, the problem of thermal damage and degradation rate during the processing process is solved, and accelerated degradation and aproton under proton conditions are achieved Maintain thermal stability under conditions.

CN113544206BActive Publication Date: 2024-12-24FRAUNHOFER GESELLSCHAFT ZUR FORDERUNG DER ANGEWANDTEN FORSCHUNG EV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080009650.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-17
Filing Date
2020-01-17
Publication Date
2024-12-24
Estimated Expiration
2040-01-17

AI Technical Summary

Technical Problem

The existing polycondensate is susceptible to thermal damage during processing and is difficult to achieve rapid degradation without damaging the stability of the material. The traditional methods are incompatible and cannot be maintained at the same time and accelerated after the intended use.

Method used

A mixture of aliphatic or cycloaliphatic polyols and organophosphorus compounds is used as a hydrolysis catalyst to catalyze the hydrolysis of the polycondensation under proton conditions, increasing the degradation rate while providing thermal stability under aproton conditions.

Benefits of technology

The hydrolysis degradation rate of the polycondensation is significantly improved, and the high thermal stability of the material is maintained in thermoplastic processing, avoiding undesired thermal degradation, and accelerating degradation is achieved without damaging the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0004944156650000021
    Figure FDA0004944156650000021
  • Figure FDA0004944156650000031
    Figure FDA0004944156650000031
  • Figure FDA0004944156650000041
    Figure FDA0004944156650000041
Patent Text Reader

Abstract

The present invention relates to the use of a mixture consisting of at least one aliphatic or alicyclic polyol, particularly sugar alcohol or cyclic alcohol and at least one organophosphorus compound as an additive to catalyze the hydrolysis (hydrolysis catalyst) of a polycondensate under protic conditions. The present invention further relates to a polycondensate composition, which comprises at least one aliphatic or alicyclic polyol, particularly sugar alcohol and / or cyclic alcohol, at least one organophosphorus compound and at least one polycondensate, and does not comprise a compound according to formula IV as defined below. Another aspect of the present invention is a molding compound or a molded part that can be manufactured by the polycondensate composition according to the present invention. Finally, the present invention relates to a method for preparing a polycondensate composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the purposes of the mixture consisting of at least one aliphatic or alicyclic polyol, particularly sugar alcohol or cyclic alcohol and at least one organophosphorus compound as an additive to catalyze the hydrolysis (hydrolysis catalyst) of polycondensates under protic conditions. The present invention further relates to polycondensate compositions, which comprise at least one aliphatic or alicyclic polyol, particularly sugar alcohol and / or cyclic alcohol, at least one organophosphorus compound and at least one polycondensate, and do not contain the compound according to formula IV defined as follows. Another aspect of the present invention is a molding compound or a molded part that can be manufactured by the polycondensate composition according to the present invention. Finally, the present invention relates to a method for manufacturing a polycondensate composition.

[0002] Polyesters such as PET or polyamides such as PA 6 are important plastics for packaging and technical applications. These plastics can be used for a long period of time for their intended use. Therefore, a high stability of the polymers towards external influences is required.

[0003] However, there has recently been an increasing demand for plastics with faster degradability. Condensation polymers are particularly suitable for meeting this demand. The reason for this is that they can be hydrolytically cleaved into low-molecular, short-chain parts with functional groups. These parts are metabolized by some microorganisms and can thus be made available to the natural metabolic cycle.

[0004] In addition, efforts in the sustainable chemistry sense are aimed at preparing polycondensation products from renewable natural resources more and more. The importance of polycondensation products such as polylactic acid (PLA), poly-3-hydroxybutyrate, poly-3-hydroxyvalerate, poly(butylene succinate) or poly(butylene succinate-co-butylene adipate) is increasing day by day. They are replacing oil-based plastics more and more frequently and have established themselves in the packaging industry and agricultural applications.

[0005] Although polycondensation products from renewable natural resources have a relatively high degradation rate and can be composted better than conventional polycondensation products, there is a need to further accelerate the degradation of these polymers. At the same time, however, problems arising during the processing of polycondensation product raw materials and thermal (pre)damage in the production of various plastic parts should be avoided.

[0006] Different approaches to accelerate degradation and stabilize preparation are already known in the literature. However, these approaches are incompatible with one another, so that polycondensate compositions that can be processed into molded parts without thermal damage and that degrade rapidly after their intended use have not previously been available.

[0007] Methods to accelerate degradation

[0008] Special environmental conditions can accelerate the degradation of polycondensates, for example by using selected microorganisms (W. Pattanasuttichonlakul et al., International Biodeterioration & Biodegradation, 2018, 132, 74-83) or enzymes (WO 2005 / 063037 A1). Another possibility is to add additives to promote degradation. On the one hand, silicon dioxide nanoparticles can be mentioned here as known to affect photocatalytic degradation (P. Georgiopoulus et al., Journal of Biomaterials Applications, 2014, 29, 662-674). Additives that promote oxidation, such as manganese stearate (CN 103408827), can also be considered. Another method to affect the degradation rate of PLA is to add inorganic fillers such as MgO or ZnO (US 2014 / 0360728 A1) or organic fillers such as chitosan or keratin (MA Elsawy et al., Renewable and Sustainable Energy Reviews 2017, 79, 1346-1352). Blends of PLA and rapidly degradable polymers can also be prepared naturally, such as blends of PLA and poly (butylene succinate) (Y. Wang et al., Polym. Bull. 2016, 73, 1067-1083).

[0009] However, the above-mentioned methods for accelerating degradation can only be used after the plastic component has been used according to its intended purpose (microorganisms, enzymes), or they bring other disadvantages. For example, photocatalysis or oxidation-promoting additives in principle change the degradation characteristics of polymers, whereas the addition of fillers or the preparation of blends with other polymers leads to materials with different mechanical properties.

[0010] Furthermore, it is known that degradation of polycondensates generally occurs only at extremely low or extremely high pH values, since acid-catalyzed or base-catalyzed cleavage of the ester groups must occur (A. Biomaterials 1996, 17, 103-114). However, acidic or alkaline environments during processing are counterproductive because severe damage to the polymer occurs.

[0011] Stable method

[0012] It is known from WO 94 / 07949 A1 that polycondensates can be stabilized by phosphites. Combinations of phosphites with other stabilizers, such as antioxidants, are also conventional and are described, for example, in WO 2010 / 000638 A1. In addition, EP 2558737 A1 discloses polycondensate compositions comprising selected phosphite stabilizers and cyclic polyols.

[0013] Other additive combinations are not known in this context.

[0014] It is therefore an object of the present invention to provide a method by which, after use according to its intended purpose, polycondensates can be stabilized in the raw product state and the degradation of molded parts produced therefrom can be accelerated. Another object of the present invention is to provide correspondingly stabilized polycondensate compositions with accelerated degradability.

[0015] The present invention therefore relates to the use of a mixture of at least one polyol (A) selected from aliphatic or cycloaliphatic polyols and at least one organophosphorus compound (B) as an additive for catalyzing the hydrolysis of polycondensates under protic conditions (hydrolysis catalyst).

[0016] A hydrolysis catalyst is understood to be a substance mixture which accelerates the hydrolytic cleavage of covalent bonds in the polycondensate and thus increases the degradation rate of the polycondensate by hydrolysis.

[0017] For example, using a comparative experiment of a polycondensation polymer comprising the mixture and a polycondensation polymer not comprising the mixture under protic conditions (e.g., in the presence of water), an increase in hydrolytic degradation can be determined. Hydrolytic degradation can be determined, for example, using a melt flow index (e.g., melt volume flow rate (MVR), determined according to EN ISO 1133-1:2011), wherein an increase in the melt flow index indicates an increase in degradation, thereby increasing the hydrolysis rate.

[0018] It was surprisingly found that by incorporating the mixture into a polycondensation polymer, the hydrolysis rate was greatly increased when the polycondensation polymer comprising the mixture was exposed to protic hydrolysis conditions.

[0019] The mixture can preferably be used simultaneously as an additive for polycondensation polymers which are thermally stable under aprotic conditions, for example in the absence of moisture.

[0020] Thermal stabilizing additives are understood to be substance mixtures which reduce the temperature-induced degradation of polycondensates. In the further processing of the original polymer, reducing the degradation is particularly important. Stabilizing additives can be used effectively, for example, in the extrusion process of polymer melts, where undesirable thermal degradation of the corresponding polymer is almost always observed.

[0021] The degree of thermal stability can be determined by measuring the molecular weight, viscosity or melt flow index, such as melt volume flow rate (MVR), before and after exposing the polycondensate to elevated temperatures. Only slight changes in the measured values ​​are indicative of a high degree of thermal stability.

[0022] Aprotic conditions are understood to mean that only molecules are present which do not have functional groups which can release hydrogen atoms as protons. Such conditions occur, for example, in thermoplastic processing of polycondensation polymers in the practical absence of moisture, in particular thermoplastic polycondensation polymers (in particular during extrusion). In contrast, under protic conditions, at least one solvent or another compound, such as water, which releases protons is present.

[0023] It was completely surprising and unforeseeable that the same mixture, while accelerating the hydrolytic degradation of the polycondensation polymer on the one hand, could simultaneously ensure the thermal stabilization of the polycondensation polymer under aprotic conditions on the other hand.

[0024] In a preferred embodiment, the polycondensate is selected from

[0025] - polyesters of aliphatic or aromatic dicarboxylic acids and diols or hydroxycarboxylic acids, for example polylactic acid (PLA), polybutylene succinate, polybutylene succinate-co-butylene adipate, poly(butylene adipate) (PBA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PPT), polyethylene naphthalate, poly-1,4-dihydroxymethylcyclohexane terephthalate, polyhydroxybenzoates, polyhydroxynaphthalates;

[0026] - polycarbonate or polyester carbonate;

[0027] - polyamides, for example PA 6, PA 6.6, PA 6.10, PA 4.6, PA 4.10, PA 6.12, PA 10.10, PA 12.12, PA 10.12, PA 11, PA 12;

[0028] - semiaromatic polyamides, such as polyphthalamides, prepared, for example, from terephthalic acid and / or isophthalic acid and aliphatic diamines or from aliphatic dicarboxylic acids, such as adipic acid or sebacic acid, and aromatic diamines, such as 1,4-phenylenediamine or 1,3-phenylenediamine;

[0029] - and mixtures, combinations or blends of two or more of the above polymers.

[0030] The polycondensate is preferably selected from PLA, poly(butylene adipate) (PBA), polycaprolactone (PCL), poly-3-hydroxybutyrate, poly-4-hydroxybutyrate, poly-3-hydroxyvalerate, poly(hexamethylene succinate), poly(butylene succinate) and copolymers, such as poly(butylene succinate-co-butylene adipate) and mixtures or blends of two or more of the above polymers.

[0031] The polycondensation polymers can be prepared by condensation reactions of α, ω functional monomers or multiple difunctional monomers, for example, with release of water using conventional technology processes. However, these polymers can also be synthesized by ring-opening polymerization; for example, polylactide (polylactic acid) is obtained from lactide by ring-opening ionic polymerization.

[0032] A mixture of at least one polyol selected from aliphatic or cycloaliphatic polyols and at least one organophosphorus compound is advantageously used as stabilizer or hydrolysis catalyst for PLA, PBA and copolymers thereof, wherein the PLA copolymer is preferably obtained by ring-opening polymerization of D-lactide and / or L-lactide with a comonomer selected from hydroxycarboxylic acids, in particular glycolic acid, 4-hydroxybutyric acid, 3-hydroxybutyric acid, 3-hydroxyvaleric acid or mandelic acid, a diol, in particular ethylene glycol or butanediol; and / or a carboxylic acid, in particular adipic acid, sebacic acid or terephthalic acid.

[0033] If the abovementioned polycondensates are copolymers, they may be present in the form of statistical (“random”) block structures or of pyramidal structures.

[0034] Furthermore, it is preferred that the at least one aliphatic or cycloaliphatic polyol (A) is selected from polyols having at least four OH groups, preferably sugar alcohols and / or cyclic alcohols having at least four OH groups, in particular selected from threitol, erythritol, galactitol, mannitol, ribitol, sorbitol, xylitol, arabitol, isomalt, inositol, lactitol, maltitol, altritol, iditol, maltotriitol, pentaerythritol, dipentaerythritol, tripentaerythritol and mixtures thereof, particularly preferably inositol and sorbitol.

[0035] The at least one organophosphorus compound is preferably selected from the group consisting of organophosphites, organophosphonites, organophosphonates, organophosphates, and mixtures and combinations thereof.

[0036] At least one organic phosphite (B) is particularly preferably contained in the mixture; it can be, for example, a readily hydrolyzable phosphite, for example a phosphite with aliphatic groups. The at least one phosphite is preferably a phosphite of the general formula (I):

[0037]

[0038] The substituent R1 , R 2 and R 3 are independently selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- and aryl radicals, or substituents R 1 Selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- and aryl radicals, and R 2 Connect to R 3 to form a ring system, in particular a spiro ring.

[0039] When at least one of the organic phosphites (B) in the mixture used has one of the following formulae (II) or (III), polycondensate compositions having very good properties are obtained:

[0040]

[0041] Where R 1 Selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- or aryl residues.

[0042] It is further preferred if mixtures are used in which at least one organic phosphite (B) is selected from the group consisting of

[0043]

[0044]

[0045] wherein n=1 to 100, preferably 2 to 10,

[0046] Or selected from trilauryl phosphite, triisodecyl phosphite, tridecyl phosphite, trihexadecylphosphite (tricetylphosphite), trioctyl phosphite, tribehenyl phosphite, trieicosanol phosphite, trihexacosanol phosphite, tricetyl phosphite and trioleyl phosphite.

[0047] Further preferred phosphites contain one or more than one benzofuranyl group as a substituent. These compounds are obtainable, for example, as described in WO 2017 / 025431 A1. The disclosure of this publication regarding the benzofuranyl substituted phosphites also forms the subject of the present patent application. Exemplary phosphites are, for example

[0048]

[0049] Furthermore, the at least one organic phosphite (B) advantageously does not contain compounds according to formula (IV)

[0050]

[0051] Where R 20 and / or R 21 Each occurrence is independently a hydrogen atom, C 1-8 -alkyl, C 5-8 -Cycloalkyl, C 6-12 -alkylcycloalkyl, C 7-12 - aralkyl or phenyl,

[0052] R 23 and R 24 Each occurrence is independently a hydrogen atom, C 1-8 -alkyl, C 5-8 -Cycloalkyl, C 6-12 -alkylcycloalkyl, C 7-12 - aralkyl or phenyl,

[0053] R 22 is a hydrogen atom or an alkyl group at each occurrence,

[0054] L 5 is a single bond, a sulfur atom or a divalent group according to formula (IVa)

[0055]

[0056] Where R 25 represents hydrogen atom, C 1-8 -alkyl or C 5-8 - cycloalkyl,

[0057] L 6 It is C 2-8 - alkylene or a divalent group according to formula (IVb)

[0058]

[0059] Where L 7 Is a single bond or C 1-8 -alkylene and * represents an oxygen binding site, and

[0060] Z 1 and Z 2 One of them is hydroxyl, C 1-8 -alkyl, C 1-8 -alkoxy or C 7-12 -aralkyloxy, the other is a hydrogen atom or a C 1-8 -alkyl.

[0061] This means that the mixtures according to the invention preferably contain no compounds according to the general formula IV.

[0062] Preferred phosphoric acid ester corresponds to the above-mentioned phosphite in structure and can for example be obtained by oxidizing these phosphites to corresponding phosphoric acid ester.Preferred phosphoric acid ester is particularly trilauryl phosphate, triisodecyl phosphate, tridecyl phosphate, trihexadecanol phosphate, trioctadecanol phosphate, tribehenyl phosphate, trieicosanol phosphate, trihexacosanol phosphate, tricetyl alcohol phosphate and trioleyl phosphate.Diphosphate and polyphosphate are further suitable.Phosphoric acid below phosphoric acid ester can also exist in the mode of only partial esterification, for example monostearyl phosphate or distearyl phosphate, or exist as the mixture of monoalkyl phosphate, dialkyl phosphate and / or trialkyl phosphate.

[0063] Preferred phosphonites are:

[0064]

[0065] In a preferred embodiment, mixtures are used in which the weight ratio of component (A) to component (B) is from 1:10 to 10:1, preferably from 1:5 to 2:1.

[0066] In a second aspect, the present invention relates to a polycondensate composition comprising or consisting of the following substances

[0067] A) at least one polyol selected from aliphatic or cycloaliphatic polyols,

[0068] B) at least one organophosphorus compound, and

[0069] C) at least one polycondensate,

[0070] And it does not contain the compound of formula (IV) defined above.

[0071] With regard to preferred embodiments in connection with the individual components (A) to (C), reference is made to the aforementioned embodiments, which also apply to the composition, without being restricted thereto.

[0072] Preferably, the polycondensate composition comprises or consists of 0.01 to 5.00 parts by weight, preferably 0.05 to 3.00 parts by weight, of at least one polyol, 0.01 to 5.00 parts by weight, preferably 0.05 to 1.00 parts by weight, of at least one organophosphorus compound, and 90.00 to 99.98 parts by weight, preferably 96.00 to 99.90 parts by weight of the polycondensate.

[0073] In addition to components (A) to (C), the polycondensate composition further comprises at least one additive selected from the group consisting of primary antioxidants, secondary antioxidants, UV absorbers, light stabilizers, metal deactivators, filler deactivators, antiozonants, nucleating agents, anti-nucleating agents, toughening agents, plasticizers, mold lubricants, rheology modifiers, thixotropic agents, chain extenders, processing aids, mold release agents, flame retardants, pigments, dyes, fluorescent whitening agents, antimicrobial active agents, antistatic agents, slip agents, anti-sticking agents, coupling agents, cross-linking agents, anti-cross-linking agents, hydrophilic agents, hydrophobic agents, adhesives, dispersants, compatibilizers, oxygen scavengers, acid scavengers, expanders, degradation additives, defoamers, odor scavengers, marking agents, anti-fogging agents, fillers, reinforcing materials, and mixtures thereof.

[0074] It is likewise possible that the polycondensate composition additionally comprises at least one further substance selected from

[0075] i) degradation additives, preferably organic transition metal compounds, such as transition metal carboxylates, in particular iron(III) stearate and / or manganese(II) stearate;

[0076] ii) a plasticizer, preferably tributyl citrate acetate, tributyl citrate, triethyl acetyl citrate, triacetin, epoxidized soybean oil and / or epoxidized linseed oil;

[0077] iii) nucleating agents, preferably talc; alkali metal or alkaline earth metal salts of monofunctional and polyfunctional carboxylic acids, in particular benzoic acid, succinic acid, adipic acid, for example sodium benzoate; aluminum hydroxybis(4-tert-butyl)benzoate; zinc glycerate; 2,2'-methylene-bis-(4,6-di-tert-butylphenyl) phosphate; triamides and diamides, for example trimethylsulfonic acid tricyclohexylamide, trimethylsulfonic acid tris(4-methylcyclohexylamide), trimethylsulfonic acid tris(tert-butylamide), N,N',N"-1,3,5-benzenetriyltris(2,2-dimethyl-propionamide), 2,6-naphthalene dicarboxylic acid dicyclohexylamide; and / or orotic acid;

[0078] iv) chain extenders, preferably diepoxides, Oxazoline, bi Oxadiazole, dimethoate Oxidizine, diisocyanate, dianhydride, bisallyl lactam, bismaleimide, dicyanate, carbodiimide and / or polymer chain extenders, such as polystyrene-polyacrylate-polyglycidyl (meth)acrylate copolymers, polystyrene maleic anhydride copolymers and polyethylene maleic anhydride copolymers;

[0079] v) Fillers, preferably calcium carbonate, silicates, talc, mica, kaolin, metal oxides, metal hydroxides, black carbon, graphite, wood flour, fibers of natural products, such as cellulose; hydrotalcite, zeolites, and / or layered silicates, for example montmorillonite, bentonite, beidellite, mica, hectorite, saponite, vermiculite, trioctahedral illite, magadiite, illite, kaolinite, wollastonite, attapulgite.

[0080] The invention further relates to a molding compound or a molded part which can be produced from the polycondensate composition described above. The molding compound or the molded part is in particular selected from injection moldings, foils, films, tapes, hollow bodies, foams and / or fibers.

[0081] Another aspect of the present invention relates to a method for producing the above-mentioned polycondensate composition, wherein a mixture consisting of at least one sugar alcohol and at least one organic phosphite is introduced into at least one polycondensate. The mixture is preferably introduced into the polycondensate in a proportion of at least 0.05% by weight.

[0082] The mixture can be introduced into the at least one polycondensate by first mixing it as a solid mixture with the at least one polycondensate and then melting the mixture thus obtained in an extruder.

[0083] Extruders, preferably equipped with vacuum degassing, such as single-screw extruders, twin-screw extruders, planetary gear extruders, ring extruders and co-kneaders are preferred as processing machines. Processing can be carried out here under air or optionally under inert gas conditions.

[0084] The mixture according to the invention can also be introduced into at least one polycondensate in the form of a masterbatch or concentrate which comprises, for example, 20 to 90% of the mixture according to the invention.

[0085] The invention also relates to the use of the polycondensate compositions described above in the following aspects: for the production of packaging, in particular packaging for foods or cosmetics; in the pharmaceutical industry, in particular for the encapsulation of active ingredients and other biologically active substances; in medical technology, in particular for the production of dressings and surgical suture materials; and / or in hygiene products, in particular as a component of disposable diapers, sanitary napkins and tampons; in agricultural applications, for example, for the production of agricultural films, such as mulch films, tunnel films or perforated films.

[0086] The invention will be described in more detail with reference to the following examples, without intending, however, to limit the invention to the preferred parameters shown.

[0087] Various polycondensate compositions (VB1-VB4 and B1-B5) were prepared.

[0088] Corbion's Luminy L 130 (≤0.5% D-lactic acid, in compliance with the certificate, MVR = 8.8 cm 3 / 10 min, measured at 190°C / 2.16 kg punch weight) was used as PLA. The polymer was dried in a vacuum oven at 80°C for at least 16 hours before processing.

[0089] The following compounds were used as additives:

[0090] Ph-a: Songnox 6260 (Manufacturer Songwon)

[0091]

[0092] Ph-b: Doverphos S 9228 (manufacturer Dover)

[0093]

[0094] Ph-d: a mixture of tristearyl phosphate, distearyl phosphate and monostearyl phosphate, commercial product ADK Stabl AX 71 from Adeka Corporation.

[0095] Al-a: Inositol (a cyclic alcohol)

[0096] Al-b: dipentaerythritol (an aliphatic polyol)

[0097] Al-c: Erythritol (a sugar alcohol)

[0098] The production of the polycondensate compositions (B1-B5) according to the invention and the comparative examples (VB1-VB4) was accomplished by extrusion using a parallel twin-screw extruder "Process 11" from ThermoScientific (screw diameter 11 mm, aspect ratio (LD) 40).

[0099] The additives were mixed manually with the matrix polymer in a plastic bag and volumetrically metered for compositions VB2-VB4 and B1-B5. The processing was carried out at 200°C with an output of 1 kg / h and a screw speed of 200 rpm.

[0100] To examine the hydrolysis rate, the polymer was stored in water at 58 °C in pellet form and the MVR was determined after 42 h or 162 h. The melt index tester MI-2 was used in the company, the test temperature was 190 ° C, and the die weight was 2.16 kg. The sample was dried in a vacuum oven at 80 ° C for at least 16 hours before the measurement. The preheating time was equal to 4 minutes. MVR is in cm 3 / 10 minutes.

[0101] The results of the processing tests are summarized in Table 1 and the results of the hydrolysis experiments are summarized in Table 2.

[0102] Table 1: Processing stability of PLA compositions

[0103]

[0104]

[0105] From the processing stability tests it can be seen that the addition of phosphites or phosphates leads to an increase in the MVR, ie an undesirable degradation of the polymer. This degradation during processing can be reduced by the combination according to the invention.

[0106] Table 2: Water storage capacity of PLA compositions

[0107]

[0108]

[0109] ND=not detected

[0110] Due to the improved processing stability of the composition according to the invention, degradation of the polymer occurs during water storage starting from a higher molecular weight (lower MVR). Therefore, it should be assumed that degradation during water storage is also delayed (which is demonstrated only by the addition of sugar alcohols), because a higher number of chain scissions is required for a specific lower molecular weight. Surprisingly, the composition according to the invention does not delay degradation, but at least keeps it unchanged or even accelerates it.

[0111] In a further series of experiments, Luminy L 175 (≤0.5% D-lactic acid, in accordance with the certificate, MVR = 4.7 cm) supplied by Corbion was used. 3 / 10 minutes, measured at 190°C / 2.16 kg die weight) as PLA.

[0112] Ph-c: Weston 618F (supplier: SI Group)

[0113]

[0114] Ph-d: Adekastab AX-71 (see above)

[0115] Al-d: Sorbitol (a sugar alcohol)

[0116] The results of the processing tests and hydrolysis tests are summarized in Table 3.

[0117] Table 3

[0118]

[0119] Compared to the test without additives, the composition according to the invention shows only a small increase in the MVR value after extrusion and an accelerated degradation during water storage, which is evidenced by the higher MVR value, i.e. the lower molecular weight. The acceleration of degradation can be monitored and set via the ratio of polyol to phosphorus, with a higher proportion of polyol contributing to processing stability and a higher proportion of phosphorus components contributing to accelerated degradation.

Claims

1. Use of a mixture consisting of the following substances as an additive to catalyze the hydrolysis of polycondensates under proton conditions A) at least one polyol selected from aliphatic or cycloaliphatic polyols selected from polyols having at least four OH groups, and B) at least one organophosphorus compound selected from the group consisting of organophosphites, organophosphonites, organophosphonates, organophosphates, and mixtures and combinations thereof, The polycondensate is selected from polyesters of aliphatic or aromatic dicarboxylic acids and diols or polyesters of hydroxycarboxylic acids, polyamides, semi-aromatic polyamides, and mixtures, combinations or blends of two or more of the above polymers.

2. The use according to claim 1 as an additive for thermally stabilizing polycondensates under protic conditions.

3. The use according to claim 1 or 2, characterized in that The polyester is polylactic acid (PLA), polybutylene succinate, polybutylene succinate-co-butylene adipate, poly(butylene adipate) (PBA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PPT), polyethylene naphthalate, poly(1,4-dihydroxymethylcyclohexane terephthalate), polyhydroxybenzoate, polyhydroxynaphthalate; The polyamide is PA6, PA6.6, PA6.10, PA4.6, PA 4.10, PA6.12, PA 10.10, PA 12.12, PA10.12, PA 11, PA 12; The semi-aromatic polyamide is polyphthalamide.

4. The use according to claim 3, characterized in that The polyphthalamide is prepared from terephthalic acid and / or isophthalic acid and an aliphatic diamine or from an aliphatic dicarboxylic acid and an aromatic diamine.

5. The use according to claim 4, characterized in that The aliphatic dicarboxylic acid is adipic acid or sebacic acid, and the aromatic diamine is 1,4-phenylenediamine or 1,3-phenylenediamine.

6. The use according to claim 1 or 2, characterized in that: The polycondensate is selected from PLA, poly(butylene adipate) (PBA), polycaprolactone (PCL), poly-3-hydroxybutyrate, poly-4-hydroxybutyrate, poly-3-hydroxyvalerate, poly(hexamethylene succinate), poly(butylene succinate) and copolymers and mixtures or blends of two or more of the above polymers.

7. The use according to claim 6, characterized in that The copolymer is poly(butylene succinate-co-butylene adipate).

8. The use according to claim 1 or 2, characterized in that: The polycondensate is selected from PLA, PBA and copolymers thereof, wherein the PLA copolymer is obtained by ring-opening polymerization of D-lactide and / or L-lactide with a comonomer selected from hydroxycarboxylic acid, diol, and / or carboxylic acid.

9. The use according to claim 8, characterized in that The hydroxycarboxylic acid is glycolic acid, 4-hydroxybutyric acid, 3-hydroxybutyric acid, 3-hydroxyvaleric acid or mandelic acid; The diol is ethylene glycol or butanediol; The carboxylic acid is adipic acid or terephthalic acid.

10. The use according to claim 1 or 2, characterized in that: The at least one aliphatic or cycloaliphatic polyol is selected from sugar alcohols and / or cyclic alcohols having at least four OH groups.

11. The use according to claim 1 or 2, characterized in that: The at least one aliphatic or alicyclic polyol is selected from threitol, erythritol, galactitol, mannitol, ribitol, sorbitol, xylitol, arabitol, isomalt, inositol, lactitol, maltitol, altritol, iditol, maltotriitol, pentaerythritol, dipentaerythritol, tripentaerythritol and mixtures thereof.

12. The use according to claim 1 or 2, characterized in that: The at least one aliphatic or alicyclic polyol is selected from myo-inositol.

13. The use according to claim 1, characterized in that At least one of the organic phosphites is a hydrolyzable phosphite.

14. The use according to claim 1, characterized in that At least one of the organic phosphites is a phosphite having the general formula I in i) Substituent R 1 , R 2 and R 3 are independently selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- and aryl radicals, or ii) Substituent R 1 Selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- and aryl radicals, and R 2 Connect to R 3 to form a ring system.

15. The use according to claim 14, characterized in that The ring system is spiro.

16. The use according to claim 1, characterized in that At least one organic phosphite has one of the following formulas (II) or (III), Where R 1 Selected from optionally substituted C4-C 32 Alkyl-, cycloalkyl- or aryl residues.

17. The use according to claim 1, characterized in that At least one organic phosphite is selected from the following compounds Where n = 1 to 100, Or selected from trilauryl phosphite, triisodecyl phosphite, tridecyl phosphite, tricetyl phosphite, trioctyl phosphite, tribehenyl phosphite, trieicosanol phosphite, trihexacosanol phosphite, tricetyl alcohol phosphite and trioleyl phosphite.

18. The use according to claim 17, characterized in that The n is 2 to 10.

19. The use according to claim 1, characterized in that The at least one organic phosphite does not contain a compound according to formula (IV) Where R 20 and / or R 21 Each occurrence is independently a hydrogen atom, C 1-8 Alkyl, C 5-8 Cycloalkyl, C 6-12 Alkylcycloalkyl, C 7-12 Aralkyl or phenyl, R 23 and R 24 Each occurrence is independently a hydrogen atom, C 1-8 Alkyl, C 5-8 Cycloalkyl, C 6-12 Alkylcycloalkyl, C 7-12 Aralkyl or phenyl, R 22 is a hydrogen atom or an alkyl group at each occurrence, L 5 is a single bond, a sulfur atom or a divalent group according to formula (IVa) Where R 25 represents hydrogen atom, C 1-8 Alkyl or C 5-8 Cycloalkyl, L 6 It is C 2-8 Alkylene or a divalent group according to formula (IVb) Where L 7 Is a single bond or C 1-8 alkylene and * indicates an oxygen binding site, and Z 1 and Z 2 One of them is hydroxyl, C 1-8 Alkyl, C 1-8 Alkoxy or C 7-12 Aralkyloxy, the other is a hydrogen atom or C 1-8 alkyl.

20. The use according to claim 1, characterized in that At least one phosphoric acid ester is selected from trilauryl phosphate, triisodecyl phosphate, tridecyl phosphate, tricetyl phosphate, trioctyl phosphate, tribehenyl phosphate, trieicosanol phosphate, trihexacosanol phosphate, tricetyl phosphate and trioleyl phosphate, diphosphates and polyphosphates, and monostearyl phosphate, distearyl phosphate and mixtures of monoalkyl phosphates, dialkyl phosphates and / or trialkyl phosphates.

21. The use according to claim 1 or 2, wherein a mixture of component (A) and component (B) is used in a weight ratio of 1:10 to 10:

1.

22. The use according to claim 1 or 2, characterized in that: A mixture of component (A) and component (B) in a weight ratio of 1:5 to 2:1 is used.